2021
DOI: 10.1063/5.0040887
|View full text |Cite
|
Sign up to set email alerts
|

The role of plasmalogens, Forssman lipids, and sphingolipid hydroxylation in modulating the biophysical properties of the epithelial plasma membrane

Abstract: A coarse-grain model of the epithelial plasma membrane was developed from high-resolution lipidomic data and simulated using the MAR-TINI force field to characterize its biophysical properties. Plasmalogen lipids, Forssman glycosphingolipids, and hydroxylated Forssman glycosphingolipids and sphingomyelin were systematically added to determine their structural effects. Plasmalogen lipids have a minimal effect on the overall biophysical properties of the epithelial plasma membrane. In line with the hypothesized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 106 publications
3
17
0
Order By: Relevance
“…Molecular simulation of bacterial membranes, and biological membranes in general, has advanced significantly over the past 20 years, with larger, more complex and more realistic simulations becoming feasible (Marrink et al 2019 ; Wilson et al 2020b ; Im and Khalid 2020 ). Advances in forcefields, particularly the CHARMM atomistic forcefield and MARTINI coarse-grained forcefield (Marrink et al 2004 , 2007 ; Wu et al 2014 ; Lee et al 2019a ), coupled with increasing hardware capabilities and improvements in simulation tooling, has enabled simulations of membranes approaching realistic chemical diversity in constituent protein and lipid components (Ingólfsson et al 2014 , 2017 ; Reddy et al 2015 ; Wilson et al 2020a , 2021 ).…”
Section: Understanding the Role Of Lipid-mediated Resistance For Anti...mentioning
confidence: 99%
“…Molecular simulation of bacterial membranes, and biological membranes in general, has advanced significantly over the past 20 years, with larger, more complex and more realistic simulations becoming feasible (Marrink et al 2019 ; Wilson et al 2020b ; Im and Khalid 2020 ). Advances in forcefields, particularly the CHARMM atomistic forcefield and MARTINI coarse-grained forcefield (Marrink et al 2004 , 2007 ; Wu et al 2014 ; Lee et al 2019a ), coupled with increasing hardware capabilities and improvements in simulation tooling, has enabled simulations of membranes approaching realistic chemical diversity in constituent protein and lipid components (Ingólfsson et al 2014 , 2017 ; Reddy et al 2015 ; Wilson et al 2020a , 2021 ).…”
Section: Understanding the Role Of Lipid-mediated Resistance For Anti...mentioning
confidence: 99%
“…Of course, the question remains to which extend the here-resolved hydrophobic pattern can prevail in nature, where evolution is subject to many additional constraints. Purely composition-wise, verification with a coarse-grained native epithelial membrane model (36) suggests that the here-resolved functionality persists in more realistic membrane environments (see Fig. S7).…”
Section: Discussionmentioning
confidence: 88%
“…A cholesterol attractor (D 3 K 3 L 8 K 3 D 3 ) was inserted into a native epithelial membrane model ((36), “Membrane 1”) and a 2 μ s NPT MD simulation is performed with a 20 fs timestep, of which the first 500 ns were used for equilibration purposes. Temperature was coupled to 310 K using velocity rescaling ( τ = 1 ps, with separate coupling groups for the membrane, peptide, and solvent).…”
Section: Supplementary Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that alterations in lipid distribution, acyl tail diversity, and lipid hydroxylation all contribute to the rate of cholesterol flip-flop. 15,16,37 Conversely, the oxidized cholesterol species flip-flop faster when the site of oxidation is on the tail group (3.89 ± 0.03 × 10 6 s −1 ) compared to when the ring is oxidized (1.43 ± 0.01 × 10 6 s −1 ). The change in rate of flip-flop between the ring-oxidized and tail-oxidized cholesterols can be explained by the difference in charge distribution across the molecule.…”
Section: ■ Results and Discussionmentioning
confidence: 99%